Neoadjuvant treatment with immune checkpoint inhibitors in patients with melanoma: A real-life retrospective study - Tomsitz, Dirk; Zimmermann, Petra; Kunz, Wolfgang G.; Neumann, Jens; Siegmund, Birte J.; Weiss, Bernhard G.; Kauke, Teresa; Sienel, Wulf; French, Lars E.; Klauschen, Frederick; Heinzerling, Lucie (Journal der Deutschen Dermatologischen Gesellschaft, 2025)
Background: Neoadjuvant treatment with ipilimumab and nivolumab has shown efficacy in melanoma patients with nodal metastases in clinical trials. Real world data on neoadjuvant therapies is lacking. Patients and Methods: This study investigates the effectiveness of neoadjuvant therapy in a real-world setting and included all melanoma patients who received combined anti-CTLA4/PD1 immunotherapy prior to resection. Pathologic and radiologic responses as well as treatment-related adverse events were assessed, and recurrence-free survival (RFS) was compared between patients with major pathologic response (mPR) and patients without mPR. Results: In total, 24 patients were analyzed, including patients with distant metastases and patients with prior adjuvant treatment. Median follow-up was 21.5 months. Upon histologic assessment, mPR was achieved in 50% (12/24) of the patients, including two patients with lung metastases and three patients who progressed after prior adjuvant anti-PD1 therapy. Radiologic response after neoadjuvant treatment correlated with mPR. No patient with mPR relapsed during follow-up (median RFS not reached) compared to six out of 12 patients without mPR (median RFS = 13 months, p = 0.005). Conclusions: Neoadjuvant treatment with ipilimumab and nivolumab is effective in real-world patients with different melanoma subtypes, different stages of disease and even advanced primary tumor.
CRIS-Team Scopus Importer:2025-04-01
Keywords: immune checkpoint inhibitors; melanoma; Neoadjuvant therapy; pathologic response